Physical Education Teacher Education Students’ Perceptions of Competencies for Sustainable Development in Their Degree Program - Salvador Baena-Morales; Andreas Fröberg; Olalla García-Taibo; Ana Isabel Ponce-Gea (Australian Journal of Environmental Education)
In an era marked by mounting global challenges, education is often envisioned as an agent of transformative action towards a more sustainable future. This research seeks to delve into the students’ perceptions concerning competencies for sustainability in Physical Education Teacher Education. Adopting a qualitative approach, a non-probabilistic purposive sample of 57 students (35 males, 22 females, mean age: 21.2 ± 3.2 years) was recruited. Data collection comprised semi-structured interviews. Analysis was facilitated through Atlas.ti v.7.5.18, abiding by established qualitative research paradigms. Participants emphasised the intrinsic value of an interdisciplinary approach. The study discerned a strong inclination towards cooperative and introspective tasks. Moreover, this exploration offers valuable insights for academic institutions, suggesting integrative strategies for environmental education. Therefore, these findings invite to adapt curricular designs, ensuring that educators are aptly prepared to respond the multifaceted challenges of the 21st century, driving our collective stride towards a sustainable, equitable future.